2013
DOI: 10.5539/elt.v6n10p235
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Metacognitive Reading Strategy Awareness in Reading Comprehension

Abstract: Metacognitive reading strategy awareness plays a significant role in reading comprehension and educational process. In spite of its importance, metacognitive strategy has long been the ignored skill in English language teaching, research, learning, and assessment. This lack of good metacognitive reading strategy skill is exacerbated by the central role of reading comprehension in education success. One solution to the problem of poor reading comprehension is the learning of metacognitive reading strategy skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 48 publications
4
135
0
11
Order By: Relevance
“…Ahmadi, Ismail and Abdullah (2013) also contended that more successful readers used metacognitive reading strategy in their reading comprehension more than the less successful readers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmadi, Ismail and Abdullah (2013) also contended that more successful readers used metacognitive reading strategy in their reading comprehension more than the less successful readers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on observing the teachers of the participating classroom, Ness found out that a total of 25% of the language arts teaching practices focused on explicit reading comprehension instruction. This score was the highest comparing to the findings of Durkin, Miller, Perkins, and Pressley et al Furthermore, remarkable research studies were implemented Ahmadi, Ismail, and Abdullah (2013), Hou (2013), and Ghavamnia, Ketabi, and Tavakoli (2013) to track comprehension strategy instruction in language learning classrooms. The overall results of these studies showed that comprehension strategy instruction developed gradually comparing to findings in previous research, nevertheless, it is still drought and far from satisfactory (Pressley, 2006;Williams, 2002).…”
Section: Scarcity Of Comprehension Strategy Instructionmentioning
confidence: 91%
“…Similarly, application of schema theory (Zhao & Zhu, 2012), use of different model of reading like class discussion, and small group discussion (Shen, 2013;Hamra & Syatriana, 2012) teaching English through MI theory (Jing, 2013), adoption of cooperative learning (Pan & Wu, 2013), use of graphic organizer (D & Rajan, 2013), adoption of reading techniques of SQ3R i.e. survey, question, read, recite and review (Attaprechakul, 2013& Mohammadi, Heidari, & Niry, 2012, use of metacognitive reading strategy (Ahmadi, Ismail, & Abdullah, 2013), use of fill in the map version of concept map technique (Soleimani & Nabizadeh, 2012), use of novel as a reading text (Tsai, 2012), use of authentic material (Guo, 2012), focus on language based approaches and strategy based approaches (Park, 2013) are found effective techniques to enhance learners' reading comprehension. In the virtual world of ELT, the use of blogs (Kashani, Mahmud, & Kalajahi, 2013) and application of blended learning (Alzumor et al, 2013) can also be beneficial for the enhancement of learners' reading comprehension.…”
Section: Teaching Reading Skillmentioning
confidence: 99%